(untitled) (Scientific journal of the Fergana State University, 2023)
In this article a compilation of syntactic and semantic features - microtext (supersynactic integrity - SSIs) as the largest text unit is provided. At the same time, functional-semantic classification of composite components of such integrity - beginning, development of thought and completeness has been studied.